The Anti-Inflammatory and Antioxidant Impact of Dietary Fatty Acids in Cardiovascular Protection in Older Adults May Be Related to Vitamin C Intake - Anna Gawron-Skarbek; Agnieszka Guligowska; Anna Prymont-Przymińska; Dariusz Nowak; Tomasz Kostka (MDPI AG, 2023)
Polyunsaturated fatty acids, such as eicosapentaenoic acid (EPA), docosahexaenoic acid (DHA), α-linolenic acid (ALA), or linoleic acid (LA), have a particular role in counteracting cardiovascular diseases. They may regulate antioxidant potential and inflammatory reactions. Little is known whether other fatty acids, such as saturated fatty acids (e.g., short-chain fatty acids (SCFA) such as butyric or caproic acid) or monounsaturated fatty acids, may be involved and whether the level of Vitamin C intake may affect these processes. The purpose of this study was to assess the impact of fatty acid intake on plasma and salivary total antioxidant capacity (TAC), and the salivary inflammation marker C-reactive protein (CRP). Eighty older adults (60-79 years old) were divided into two groups with high (n = 39) and low (n = 41) Vitamin C intake. In the group with high Vitamin C intake SCFA, ALA, LA positively correlated with the plasma TAC indices, and in the group with low Vitamin C intake, the salivary TAC was decreased in subjects with a higher SCFA intake. Salivary CRP negatively corresponded to SCFA, EPA, and DHA in the whole study group (p < 0.05 for all). Fatty acids and Vitamin C intake may influence antioxidant potential and salivary CRP.